Left ventricular septal pacing versus left bundle branch pacing in the treatment of atrioventricular block - Yu Zhou; Jinfeng Wang; Youquan Wei; Wenbo Zhang; Yuwen Yang; Shibao Rui; Changlin Ju (Annals of Noninvasive Electrocardiology, 2022)
Abstract Background This study aimed to evaluate the feasibility and clinical response of LVSP as an alternative to LBBP. Methods This was a retrospective study of pacemaker implantation, and 46 consecutive patients with pacemaker implantation were enrolled in the study. The patients were divided into the LBBP and LVSP groups. Electrocardiogram characteristics, pacing parameters, cardiac function, and safety events were assessed during implantation and 12‐month follow‐up. Results The procedure time was significantly increased in the LBBP group compared with the LVSP group (53.52 ± 14.39 min vs. 38.13 ± 11.52 min, respectively, p = .000). The pacing QRS duration (PQRSD) decreased by 14.09 ± 41.80 ms in the LBBP group and increased by 9.70 ± 29.60 ms in the LVSP group (p = .031). Furthermore, the left ventricle activation time (LVAT) was shorter in the LBBP group than in the LVSP group (48.70 ± 13.67 ms vs. 58.70 ± 13.67 ms, p =  .032). During the 12‐month follow‐up, pacing thresholds remained low and stable, and there was no significant decrease in cardiac function. No adverse event was observed during the follow‐up period. Conclusions Both LBBP and LVSP are safe and feasible methods. LVSP is a good option when multichannel electrophysiological instruments are not available and when the time available for the procedure is limited.